Downward Nominal and Real Wage Rigidity: Survey Evidence from European Firms - Jan Babecký; Philip Du Caju; Theodora Kosma; Martina Lawless; Julián Messina; Tairi R\~o\~om (European Central Bank (ECB), 2009)
It has been well established that the wages of individual workers react little, especially downwards, to shocks that hit their employer. This paper presents new evidence from a unique survey of firms across Europe on the prevalence of downward wage rigidity in both real and nominal terms. We analyse which firm-level and institutional factors are associated with wage rigidity. Our results indicate that it is related to workforce composition at the establishment level in a manner that is consistent with related theoretical models (e.g. efficiency wage theory, insider-outsider theory). We also find that wage rigidity depends on the labour market institutional environment. Collective bargaining coverage is positively related with downward real wage rigidity, measured on the basis of wage indexation. Downward nominal wage rigidity is positively associated with the extent of permanent contracts and this effect is stronger in countries with stricter employment protection regulations.
Keywords: J30; J31; J32; C81; P5; 330; Downward nominal wage rigidity; Downward real wage rigidity; European Union; survey data; wage indexation; Lohnrigidität; Lohnindexierung; EU-Staaten